Investigating the endophytic competency and pathogenicity efficacy of Beauveria bassiana isolates against Chilo partellus Swinhoe - Bancole, W.B.A.; Laing, M.; Yobo, K.S.; Togola, A.; Saeed, M.B. (Springer, 2022)
Sorghum bicolor L. Moench (Poaceae) is a cereal crop grown worldwide and playing an important role in human nutrition as well as feed for livestock. Lepidopteran stem borers are the most economically important insect pests that affect sorghum production and their management relies on the use of insecticide chemicals that have adverse effects on humans and biodiversity. The objective of this study was to investigate the endophytytic and pathogenic properties of Beauveria bassiana (Balsamo) Vuillemin as environmentally friendly, ecologically sound and sustainable bioncontrol method against Chilo partellus Swinhoe, one of the key stemborer of Sorghum in South Africa. In this study, 20 strains of Beauveria bassiana (Balsamo) Vuillemin were tested on sorghum cultivars Sugargraze AS 18, AS 79, AS 71 and PAN 8816 initially infested with Chilo partellus Swinhoe at 3rd instar larval stage. For the purpose, various strains of B. bassiana were inoculated in sorghum cultivars as foliar spray or seed treatment inoculum. At 30 and 60 days after the inoculation, the roots, stems and leaves of the cultivars were sampled to evaluate the endophytic property of each B. bassiana strain. Moreover, the 3rd instar larvae of C. partellus were fed with harvested stems previously colonized by the five best strains of B. bassiana to test their pathogenicity. Some 3rd instar larvae were fed with untreated stems (check). On both treated and untreated plants, number of dead larva was counted and recorded every seven days for 28 days interval.